Unlocking "lock-in" and path dependency: A review across disciplines and socio-environmental contexts. (January 2023) - Goldstein, Jenny E.; Neimark, Benjamin; Garvey, Brian; Phelps, Jacob
Highlights: Lock-in has been widely adopted to explain the challenges of transitioning away from fossil fuels. Review demonstrates that entrapment is not simply infrastructural and sub-optimal innovations Identify crosscutting reasons for why, how, and when lock-in emerges. Broadens utility of lock-in to entrenchment in complex socio-environmental systems. Abstract: Introduced in the early 2000s, the concept of carbon "lock-in" has been widely adopted by think tanks, academics, and civil society trying to break away from the consequences of fossil-fuel induced carbon emissions and climate change. The concept has been instrumental to energy economic policy, energy transitions, and automobile transportation and urban mobility. It has parallels with "path dependency" across sectors, including water governance, fisheries, farmer tenure, and debt. Yet its use has also fallen short in applying it to nontechnical settings beyond infrastructure. In this review article, we argue that the "lock-in" concept is relevant to a much broader range of multi-scalar socio-environmental challenges to development. We expand lock-in to consider granular issues that tend to slip out of macro-level technological and institutional path dependencies, without falling into the 'naturalizing trap' in systems thinking. Broadening and re-engaging the concept of lock-in strengthens our analytical ability to address a range of structurally uneven environmental and societal lock-ins.